Characterization of bovine production system typologies on indigenous reservations (Etnia-Pijao) at Natagaima-Tolima, Colombia - Ortiz-Valdes, Ciro; Velázquez-Penagos, José; Pastrana-Aguirre, Gloria; Arguelles-Cárdenas, Jorge; Flórez-Díaz, Hernando; Pérez-Guerrero, Yohaira (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
In southern Tolima, Colombia, the Indigenous Reservations (IR) of the Pijao ethnic group depend on cattle ranching, but their productive dynamics are poorly understood, making it difficult to design sustainable models. The objective of this study was to characterize the emerging typologies of the bovine production system of these IR by considering the sociocultural, techno-economic, and environmental processes. In 2023, a semi-structured interview was conducted in fifteen production units (PU) of the twenty-nine existing in the area. Indicators from each dimension (techno-economic, sociocultural, and environmental) were analyzed through multivariate analysis, identifying three typologies: G1 (46.6 %), composed by small IRs whith technology low level, showing a small-scale production; G2 (26.7 %), also grouped small IRs with small-scale production but moderately technified; and G3 (26.7 %) was integrated by large IRs, moderately technified and with a medium scale production. G3 stood out for some indicators of the techno-economic dimension. Although, all groups showed a low level of technological adoption, which resulted in poor productive and reproductive performance. The differences in G3’s better economic outcomes are due to its larger scale of production. In the social sphere, female leadership stood out, especially in groups with the highest proportion of trained people (G2 and G3). Overall, the PUs showed soils with poor organic matter content, low fertility level, little forest coverage and a moderate degree of erosion, indicating some alterations of the agroecosystem.